Socioecological influencers of health-promoting lifestyles in Chinese: a preliminary survey using convenient samples - Huang, Li; Li, Hansen; Liu, Haowei; Tian, Haodong; Luo, Haoyue; Wu, Jinlong; Luo, Yue; Peng, Li; Guo, Liya (Frontiers in Public Health, 2024)
Background: Healthy lifestyles are considered important means to reduce the burden of diseases. This cross-sectional study was conducted based on the Ecological Model of Health Behavior (EMHB) to analyze the factors associated with the health-promoting lifestyles of Chinese residents.Methods: We carried out a cross-sectional investigation in July 2023. Our investigated factors included social-demographic characteristics (including sex, age, education level, employment status, marital status, personal monthly income, and daily behavioral habits, which were measured by a questionnaire), health literacy (which was measured by the Chinese version of the Health Literacy Scale Short-Form scale (HLS-SF12)), and family health (which was measured by the Chinese Version of the Short-Form of the Family Health Scale (FHS-SF)). Our outcome was health promoting lifestyle, which was measured by a revised version of Health Promoting Lifestyle Profile-Ⅱ (HPLP-ⅡR). Data were analyzed using stepwise regression.Results: A total of 1402 participants were enrolled. Higher scores of HLS-SF12 (β=0.467), having regular exercise (β=0.212), and regular physical examinations (β=0.088) were associated with better health-prompting lifestyles. However, older age (≥60 years) (β=-0.046), drinking (β= -0.066), and sleeping time (5-6 hours/day) (β= -0.048) showed lower levels of health-prompting lifestyles. Living with family (β=0.077), FHS-SF (β=0.104), and married (β=-0.077) were significant influencers. Unemployed (β=-0.048), receiving retirement pay (β=-0.053), and economic support provided by parents (β=0.094) were associated with better health-prompting lifestyles. The terms of the six dimensions of the HPLP-ⅡR, there are multiple main influencing factors. Our findings indicate that community residents with higher health literacy, better family health, and health-related behaviors tend to have better health-promoting lifestyles.2 Conclusion: Our findings have confirmed the complex impacts of social-ecological factors on healthpromoting lifestyles, which may help policy makers with health-promotion strategies making and also help researchers to control for confounding in study design.